Pendistribusian Dana Ziswaf Di Masa Pandemi Covid-19: (Studi Analisis Terhadap Lazisnu Kota Kediri) - Adhitya, Toni (Al-Muhasib: Journal of Islamic Accounting and Finance, 2021)
This research is motivated by the spread of the Covid-19 pandemic in various countries, especially Indonesia, which hurts the state order. These impacts cover the economic, educational, health, social, and religious fields. In handling the impact of Covid-19, it is necessary to collaborate with the government and elements of the community, especially zakat management institutions as social fund management institutions. The purpose of this study is to find out how the mechanism for the distribution of ZISWAF in dealing with the Covid-19 pandemic and the role of ZISWAF in dealing with the Covid-19 pandemic in affected communities. As well as the distribution of ZISWAF in dealing with the Covid-19 pandemic at LAZISNU Kediri. The results showed that the ZISWAF distribution during the pandemic was manifested in various programs and several factors supported and hindered the distribution.